PENGAWASAN TERHADAP BENDAHARA PENGELUARAN PEMBANTU PADA DINAS PEKERJAAN UMUM KOTA PONTIANAK - Retnowati E.21108054, Neni (FISIP Universitas Tanjungpura, 2013)
Basically management in an organization consists of four inter-related pillars, and one of the pillars of oversight is conducted by a leader against the work of its employees. Supervision carried out with the aim to prevent the occurrence of deviations and to compare the results with the employee the standards already set. This study focused on the implementation of the supervision that consists of direct supervision, indirect supervision, and supervision based on exceptions. To discuss the focus of the study, used qualitative methods and case study research conducted in the Dinas Pekerjaan Umum Kota Pontianak. Based on the results of the study found that the implementation of the supervision in the financial part is still less than optimal so that several irregularities that often delay reporting SPJ (Letter of Responsibility), and one reason is the lack of supervision of the work of the leadership of the employees. Therefore, researchers suggest that leaders can optimize the direct supervision of the work of employees so that if errors are found in the work of an employee can be immediately corrected. Leaders are expected to be more prudent in correcting employee reports to avoid mistakes when making important decisions. If a fatal error occurs from the work of employees, leaders should implement monitoring by exception is to combine direct supervision and indirect supervision.Keywords: Monitoring Direct, Indirect Supervision, Supervision Based on Exceptions.